Metals-triggered compound CDPDP exhibits anti-arthritic behavior by downregulating the inflammatory cytokines, and modulating the oxidative storm in mice models with extensive ADMET, docking and simulation studies - Hassan, Syed Shams ul; Abbas, Syed Qamar; Muhammad, Ishaq; Wu, Jia-Jia; Yan, Shi-Kai; Ali, Fawad; Majid, Muhammad; Jin, Hui-Zi; Bungau, Simona (Frontiers in Pharmacology, 2022)
Graphical Abstract